Bijuridismo, bilingüismo y terminología jurídica en francés: el caso canadiense - Jiménez Salcedo, Juan (Anales de Filología Francesa, 2010)
The article presents French jurislinguistics in Canada, which has created a new terminology for common law in French. It describes how Canadian legislation and case law establishes bilingualism in the judicial system and how scholars have managed to produce common law bilingual glossaries.